Mutation of the Traj18 gene segment using TALENs to generate Natural Killer T cell deficient mice - Zhang, Jingjing (Sci Rep, 2016)
Invariant Natural Killer T (iNKT) cells are a unique subset of T lymphocytes that have been implicated in both promoting and suppressing a multitude of immune responses. In mice, iNKT cells express T cell antigen receptors (TCRs) comprising a unique TCRα rearrangement between the Trav11 and Traj18 gene segments. When paired with certain Trbv TCRβ chains, these TCRs recognize lipid antigens presented by the major histocompatibility complex (MHC) class I-like molecule, CD1d. Until recently, the sole model of iNKT deficiency targeted the Jα18, which is absolutely required to form the TCR with the appropriate antigenic specificity. However, these mice were demonstrated to have a large reduction in TCR repertoire diversity, which could confound results arising from studies using these mice. Here, we have created a new NKT-deficient mouse strain using transcription activator-like effector nuclease (TALEN) technology to only disrupt the expression of Jα18, leaving the remaining Jα repertoire unperturbed. We confirm that these mice lack iNKT cells and do not respond to lipid antigen stimulation while the development of conventional T cells, regulatory T cells, and type Ib NKT cells is normal. This new mouse strain will serve as a new model of iNKT cell deficiency to facilitate our understanding of iNKT biology.